(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The performance of seed tubers harvested from potato plants grown from sprout cutting, stem cutting and conventional seed tubers against PVY and PLRV were investigated. Sprout cutting, stem cutting and conventional seed tubers of variety Diamant were planted and second and third generation seed tubers were harvested. The least incidence of PVY and PLRV was recorded when seed tubers from sprout cutting were used. Whereas, the highest incidence of the viruses was observed where conventional seed tubers wete planted. Incidence of PVY, PLRV and their mixed infection was lower in earlier generations as compared to later generations. Performance of seed tubers produced from sprout cutting was better in respect of plant growth, tuber number and tuber yield per hill as compared to seed tubers obtained from stem cutting or conventional method. Key Words: Sprout cutting; stem cutting; PVY; PLRV; growth; yield; potato. DOI: 10.3329/bjar.v34i4.5837 Bangladesh J. Agril. Res. 34(4) : 609-622, December 2009